2018
DOI: 10.18520/cs/v114/i06/1174-1180
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Patterns of Indian Scientists in Organic Chemistry

Abstract: An analysis of 17,344 papers published by Indian scientists and indexed by Web of Science in the discipline of organic chemistry during [2004][2005][2006][2007][2008][2009][2010][2011][2012][2013] indicates that collaborative coefficient has increased during the later years (2011)(2012)(2013). Of the total published papers, 6312 (36.4%) were due to domestic and international collaboration. The share of papers in domestic collaboration was 77.3% ( 4882) and international collaboration was 22.7% ( 1430). Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This is in good agreement with the quality and prestigious of journals, i.e. low impact factor journals have more uncitedness rate, but the high impact factor journals are not immune from uncitedness (Garg and Kumar, 2014; Miranda and Garcia-Carpintero, 2019).…”
Section: Resultssupporting
confidence: 77%
“…This is in good agreement with the quality and prestigious of journals, i.e. low impact factor journals have more uncitedness rate, but the high impact factor journals are not immune from uncitedness (Garg and Kumar, 2014; Miranda and Garcia-Carpintero, 2019).…”
Section: Resultssupporting
confidence: 77%
“…There is an increasing demand for collaborative relationships among individuals, organizations, and countries. International collaboration in scientific research has increased rapidly in recent decades [4], particularly in the biological sciences [15]. It is worth mentioning, that the collaboration in biology has increased substantially and takes different shapes in field and laboratory work.…”
Section: библиометрия -сотрудничество -библиометрические показателиин...mentioning
confidence: 99%
“…CC tends to zero as single-authored papers dominate and to (1 -1/j) as j-authored papers dominate. This implies that the higher the value of CC, the higher the probability of multi-authored papers [4].…”
Section: библиометрия -сотрудничество -библиометрические показателиин...mentioning
confidence: 99%
“…It was found that there is noticeable difference between the US under study in terms of productivity. Garg, Kumar and Beb (2018) 6 analysed the publication output of Indian Scientists in the field of organic chemistry during 2004 and 2013 covered in the Web of Science. The study indicates that collaboration coefficient has increased during 2011 and 2013.…”
Section: Review Of Related Literaturementioning
confidence: 99%